2012
DOI: 10.4314/just.v32i2.6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Antifungal Susceptibility of Candida Species Isolated from Women Attending a Gynaecological Clinic in Kumasi, Ghana

Abstract: Candidal vulvovaginitis causes extreme discomfort and affects the well being of women. The aim of this study was to determine the prevalence of Candida infections among women attending gynaecological clinic at the Komfo Anokye Teaching Hospital (KATH) in Kumasi and the antifungal susceptibility patterns of the Candida species isolated. A total of 186 high vaginal swabs (HVS) were collected from women suspected of having candidal vulvovaginitis between March and June 2009. Wet mount preparations in potassium hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
14
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 16 publications
7
14
2
Order By: Relevance
“…A similar result was obtained in a study in Ghana where 21% prevalence was reported (Abruquah, 2012;Feglo and Narkwa, 2012). The high incidence rate (25.0%) recorded in the 23-25 age group in our study agrees with the 25.6% reported by Abruquah (2012) in Ghana among a similar age group. This may suggest a tentative silent Candida infection that may become wide spread among females.…”
Section: Methodssupporting
confidence: 92%
See 1 more Smart Citation
“…A similar result was obtained in a study in Ghana where 21% prevalence was reported (Abruquah, 2012;Feglo and Narkwa, 2012). The high incidence rate (25.0%) recorded in the 23-25 age group in our study agrees with the 25.6% reported by Abruquah (2012) in Ghana among a similar age group. This may suggest a tentative silent Candida infection that may become wide spread among females.…”
Section: Methodssupporting
confidence: 92%
“…A prevalence of 22% in both adolescent and adults has been reported in the USA (Reed, 1992). A similar result was obtained in a study in Ghana where 21% prevalence was reported (Abruquah, 2012;Feglo and Narkwa, 2012). The high incidence rate (25.0%) recorded in the 23-25 age group in our study agrees with the 25.6% reported by Abruquah (2012) in Ghana among a similar age group.…”
Section: Methodssupporting
confidence: 91%
“…Epidemiological data on chronic and recurrent forms of vulvovaginal candidiasis that do cause significant morbidity and discomfort are nonexistent in RoC. However, a study in 2012 reported the prevalence of vulvovaginal candidiasis among Ghanaian women at 21% in a gynaecology clinic 70 and it is likely that a similar pattern of frequency would be seen in RoC. Considering the local healthcare facilities, it is unlikely that infected women have access to dedicated medical advice for such kinds of infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented the aetiology, pathogenesis, immunity and development of vaccines for Candida species that have been causing RVVC in women in different parts of the world (Sobel, 2002;Cassone, 2015). However, in Ghana there are paucity of studies on the aetiology of RVVC especially infections caused by Candida species (Apea-Kubi et al, 2005;Abuquah, 2012;Essel et al, 2014). Even in those studies the virulent factors associated with the Candida species were not reported.…”
Section: Introductionmentioning
confidence: 99%